Factors associated to COVID-19 vaccine acceptance in Mexican patients with rheumatic diseases: A cross-sectional and multicenter study. Issue 5 (30th November 2022) - Guaracha-Basañez, Guillermo Arturo; Contreras-Yáñez, Irazú; Álvarez-Hernández, Everardo; Reyes-Cordero, Greta; Flores-Alvarado, Diana Elsa; González-Chávez, Susana Aidée; Galarza-Delgado, Dionicio Ángel; Martínez-Leyva, Perla Rocío; Moctezuma-Ríos, José Francisco; García-García, Conrado; Medrano-Ramírez, Gabriel; Gastelum-Strozzi, Alfonso; et al.
ABSTRACT: COVID-19 vaccination is recommended in patients with rheumatic diseases (RDs) to prevent hospitalized COVID-19 and worse outcomes. However, patients' willingness to receive a SARS-CoV-2 vaccine and the associated factors vary across populations, vaccines, and time. The objective was to identify factors associated with COVID-19 vaccine acceptance (VA) in Mexican outpatients with RDs. This multicenter study was performed between March 1 and September 30, 2021, and four national centers contributed with patients. Participants filled out a questionnaire, which included 32 items related to patients' perception of the patient-doctor relationship, the COVID-19 vaccine component, the pandemic severity, the RD-related disability, comorbid conditions control, immunosuppressive treatment impact on the immune system, and moral/civil position of COVID-19 vaccine. Sociodemographic, disease-related, and treatment-related variables and previous influenza record vaccination were also obtained. Multiple logistic regression analyses identified factors associated with VA, which was defined based on a questionnaire validated in our population. There were 1439 patients whose data were analyzed, and the most frequent diagnoses were Rheumatoid Arthritis in 577 patients (40.1%) and Systemic Lupus Erythematosus in 427 (29.7%). Patients were primarily middle-aged women (1235 [85.8%]), with (mean±SD) 12.1 (±4.4) years of formal education. Years of education, corticosteroid use, patient perceptions about the vaccine and the pandemic severity, patient civil/moral position regarding COVID-19 vaccine, and previous influenza vaccination were associated with VA. In Mexican patients with RDs, COVID-19 VA is associated with individual social-demographic and disease-related factors, patient´s perceptions, and previous record vaccination. This information is crucial for tailoring effective vaccine messaging in Mexican patients with RDs.